Advancing Regenerative Cellular Therapies in Non-Scarring Alopecia - Talagavadi Channaiah Anudeep; Madhan Jeyaraman; Sathish Muthu; Ramya Lakshmi Rajendran; Prakash Gangadaran; Prabhu Chandra Mishra; Shilpa Sharma; Saurabh Kumar Jha; Byeong-Cheol Ahn (MDPI AG, 2022)
Alopecia or baldness is a common diagnosis in clinical practice. Alopecia can be scarring or non-scarring, diffuse or patchy. The most prevalent type of alopecia is non-scarring alopecia, with the majority of cases being androgenetic alopecia (AGA) or alopecia areata (AA). AGA is traditionally treated with minoxidil and finasteride, while AA is treated with immune modulators; however, both treatments have significant downsides. These drawbacks compel us to explore regenerative therapies that are relatively devoid of adverse effects. A thorough literature review was conducted to explore the existing proven and experimental regenerative treatment modalities in non-scarring alopecia. Multiple treatment options compelled us to classify them into growth factor-rich and stem cell-rich. The growth factor-rich group included platelet-rich plasma, stem cell-conditioned medium, exosomes and placental extract whereas adult stem cells (adipose-derived stem cell-nano fat and stromal vascular fraction; bone marrow stem cell and hair follicle stem cells) and perinatal stem cells (umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs), Wharton jelly-derived MSCs (WJ-MSCs), amniotic fluid-derived MSCs (AF-MSCs), and placental MSCs) were grouped into the stem cell-rich group. Because of its regenerative and proliferative capabilities, MSC lies at the heart of regenerative cellular treatment for hair restoration. A literature review revealed that both adult and perinatal MSCs are successful as a mesotherapy for hair regrowth. However, there is a lack of standardization in terms of preparation, dose, and route of administration. To better understand the source and mode of action of regenerative cellular therapies in hair restoration, we have proposed the "À La Mode Classification". In addition, available evidence-based cellular treatments for hair regrowth have been thoroughly described.